Development of heuristics for transparent optical networks dimensioning - Fernandes, Eduardo José Domingues (2019)
In this dissertation a set of heuristic algorithms was developed, implemented and validated for the dimensioning of transparent optical networks. A generic platform was also created in order to allow the heuristics development and implementation, based on two main entities: a logical layer manager and a physical layer manager. The referred structure was designed in order to allow the test of a vast variety of heuristic algorithms. Within the scope of this dissertation were developed traffic scheduling algorithms based on the individual traffic quantity of each request. In addition, some routing, grooming and wavelength assignment algorithms were also developed. The main goal of these heuristics is is to dimension networks, while recurring to the minimum possible amount of resources, thus minimizing the CAPEX of the network, while also trying to guarantee the total traffic routing. For simplicity reasons only the case of networks without survivabilty was treated, although the platform is sufficiently generic to allow its inclusion in future work. Regarding the economic aspects, a detailed and comparative study was conducted, focusing on the networks CAPEX, in order to validate and assess the quality of the solutions provided by the heuristics developed based on the solutions given by an integer linear programming model. Finally, some conclusions and possible future work are discussed.